The Training of Health Cadre as an Effort to Prevent the Transmission of HIV/AIDS to Pregnant Women - Dame Evalina Simangunsong; Kandace Sianipar; Juliani Purba (MITRA: Jurnal Pemberdayaan Masyarakat, 2021)
The degree of public health in a country can be reflected in the number of health cases resulting in maternal and infant mortality. The mortality rates can further increase with the cases of HIV transmission from mother to child. Therefore, to mitigate this issue, there should be a program that can provide basic health services. One such program was once conducted in the Center for Public Health through VCT services. However, this program did not manage to lower the case counts as expected. The presence of midwives in the health facilities is observed to be inadequate in attracting pregnant women to undergo ANC services. Furthermore, there are still cases of delay in the pregnant women’s first visit to the health service, rendering it too late to identify pregnant women with HIV. The Mitra Village Development Program (PPDM) in Dolok Hataran Village, Siantar District, Simalungun Regency, was then conducted and enhanced the health cadres’ knowledge about the measures taken to prevent HIV/AIDS transmission from pregnant women to their babies, also able to provide counseling practices. The method of activity is training of 24 health cadres of Batu Anam Health Center, Simalungun Regency, and counseling practices with pregnant women. This activity succeeded in increasing the knowledge of cadres and cadres able to conduct counseling practices.